Hubungan Kepuasan Kerja dengan Kinerja Perawat di Rumah Sakit - Raja Syafrizal; Yulihasri Yulihasri; Zifriyanthi Minanda Putri (Universitas Batanghari Jambi, 2021)
The performance of nurses can be seen from several cases that occur in hospitals. The incidence of falls in patients, nosocomial infections, inadequate documentation is the result of nurses' low performance. Factors that affect the performance of nurses in hospitals are job satisfaction. So this study aims to describe the relationship between job satisfaction and nurse performance. This study used a cross-sectional study design with a sample of 85 nurses at Arosuka Hospital using proportional sampling technique. The research instrument used a job satisfaction survey questionnaire and the Individual Work Performance quasi (IWPQ) and statistical tests used frequency distribution and chi-square tests. The results showed that the majority of nurses' job satisfaction was in the satisfied category as much as 56.5% and the majority of nurses' performance in the high category was 51.8%. Then obtained a significant relationship between job satisfaction and nurse performance with a p-value of 0.000. So it is expected that hospitals can pay attention to aspects of nurse job satisfaction in making policies